The role of brand authenticity in enhancing consumer trust in msme products - Muhamad Malik Mutoffar (Institute of Computer Science (IOCS), 2026)
Consumer trust is increasingly important for Micro, Small, and Medium Enterprises (MSMEs) operating in social-commerce environments, where consumers face uncertainty regarding product quality, seller credibility, and brand claims. However, empirical evidence regarding the relationship between brand authenticity and consumer trust among Indonesian MSMEs on TikTok Shop remains limited. This study aims to examine the relationship between perceived brand authenticity and consumer trust in MSME products sold through TikTok Shop. A quantitative cross-sectional survey was conducted among 152 TikTok Shop users selected using purposive sampling. Respondents were active TikTok users aged 17 years or older who had purchased MSME products through TikTok Shop within the previous three months. Data were collected using a five-point Likert-scale questionnaire and analyzed using simple linear regression after validity, reliability, normality, and heteroscedasticity assessments. The results indicate a positive and statistically significant relationship between brand authenticity and consumer trust, with a regression coefficient of 0.687 and a significance value of p < 0.001. The coefficient of determination (R²) of 0.472 indicates that brand authenticity explains 47.2% of the observed variance in consumer trust, while the remaining 52.8% is associated with factors outside the model. These findings extend research on brand authenticity and consumer trust in the Indonesian MSME social-commerce context and suggest that authentic brand communication can strengthen consumer confidence. However, the cross-sectional design and purposive sampling limit causal inference and generalization